Study of the temperature uniformity of aluminium billets heated by superconducting DC induction heaters. Issue 1 (5th January 2015) - Wang, Yawei; Gao, Hao; Li, Zhuyong; Ping, Yang; Jin, Zhijian; Hong, Zhiyong
Abstract : Purpose: – The purpose of this paper is to analyse and improve the temperature uniformity of aluminium billets heated by superconducting DC induction heaters. Design/methodology/approach: – A 3D electromagnetic model coupled with a heat transfer model is developed to calculate the heating process of the billets which are rotated in uniform transverse DC magnetic field. A laboratory-scale DC induction heater prototype has been built to validate the model. The results from simulation and measurement have a good agreement. The model is used to investigate the factors affecting the temperature uniformity of aluminium billets. Findings: – The results from simulation show that lower rotation speeds always mean better temperature uniformity along the radial direction, due to the increase in power penetration. However, the situation is very different for the temperature distribution along the axial direction. When the rotation speed is low, the temperature at the ends is lower than other parts. The situation reverses as the rotation speeds increase. This phenomenon is referred to as the "ending effect" in this paper. Research limitations/implications: – Because of the ending effect, a lower rotation speed does not always result in better overall temperature uniformity, especially for billets of smaller sizes. Practical implications: – There is an optimal rotation speed that yields the best overall temperature uniformity. Lower rotation speeds are not always preferred. The results and numerical model developed are very useful in the design of a superconducting DC induction heater. Originality/value: – The temperature uniformity of aluminium billets heated by DC induction heaters is investigated and optimized.